1982
DOI: 10.1021/ja00387a065
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the activation parameters for automerization of cyclobutadiene-1,2-d2

Abstract: In this communication we report temperature and concentration dependence studies on the trapping of vicinally dideuterated cyclobutadiene in dichloromethane solution. The results allow limits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 0 publications
6
100
0
2
Order By: Relevance
“…[40] To summarize, the present theoretical results provide strong computational evidence that isomers 1 and 3 are bond-stretch isomers, thus enriching a set of these very rare species encompassing 1,2-and 1,8-dichloroperfluoro-cyclooctatetraene pair, [7] as well as cyclobutadiene as a special case. [6] It is, therefore, hoped that our results will stimulate additional synthetic efforts to prepare both isomers in pure or substituted forms. A judicious choice of substituents should be helpful in this respect, as discussed in the preceding paper.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[40] To summarize, the present theoretical results provide strong computational evidence that isomers 1 and 3 are bond-stretch isomers, thus enriching a set of these very rare species encompassing 1,2-and 1,8-dichloroperfluoro-cyclooctatetraene pair, [7] as well as cyclobutadiene as a special case. [6] It is, therefore, hoped that our results will stimulate additional synthetic efforts to prepare both isomers in pure or substituted forms. A judicious choice of substituents should be helpful in this respect, as discussed in the preceding paper.…”
Section: Discussionmentioning
confidence: 87%
“…[5] The situation is more promising in organic chemistry. In addition to the paradigmatic cyclobutadiene automerization interconversion, [6] there is a well-established pair of bond-stretch isomers: 1,2-and 1,8-dichloroperfluorocyclooctatetraenes. [7] However, these systems are more exceptions than a rule, and the bottom line is that the experimental detection of bond-stretch isomerism turned out to be extremely difficult and elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The barrier height has been measured to be in the range 1.6-10 kcal/mol [96,97]. The stabilization energy ∆E(1 1 B 1g − 1 1 A g ) going from square to rectangular geometry has been calcultated [85][86][87][88][89][90][91]93,94,98] between 5 and 13 kcal/mol according to the results of Table 4.…”
Section: Structural Instabilitiesmentioning
confidence: 99%
“…It dimerizes in solid matrices at ! 35 K, is a transient reactive intermediate in solution, and has a lifetime of only 2 ms at 0.1 Torr in the gas phase.[1a] Nevertheless, trapping [4] and spectroscopic results have revealed that cyclobutadiene has a ground-state singlet configuration and adopts a rectangular D 2h structure which rapidly undergoes automerization. An isolable and room temperature stable complex consisting of 1 in the cavity of a spherical crown ether (that is, a hemicarceplex) has even been prepared, [5] but the thermodynamic stability of cyclobutadiene remains experimentally unknown.…”
mentioning
confidence: 99%